A critical review on co-gasification and co-pyrolysis for gas production. (June 2022) - Mariyam, Sabah; Shahbaz, Muhammad; Al-Ansari, Tareq; Mackey, Hamish. R; McKay, Gordon
Abstract: Sustainable energy resources are a solution to the increasing energy demand caused by the accelerating population growth and the national development in the emerging countries. Biomass wastes, such as municipal solid wastes, sewage sludge, and agriculture wastes have potential to be converted into energy via thermochemical processing methods - pyrolysis and gasification. These waste treatment methods are environmentally friendly compared to direct burning and other advantages include: a reduced carbon footprint, waste emission reduction, abundant availability, and comparable energy efficiencies. The types and quantity of value-added products depend on process types and operating parameters - temperatures, catalyst, particle size and waste type. This review focuses on the production of gaseous fuel, especially syngas, from the co-conversion of biomass with other waste using the co-gasification and co-pyrolysis processes. This review critically discusses experimental and modelling studies and the key parameters - synergistic effects, reactor types, catalyst types, blending ratio, pre-treatments processes, performance efficiencies, and gasifying agents. Results reflect that mixing coal with biomass significantly reduces SO2, NOxs, and tar yields while increasing gas yields. The co-conversion of biomass and plastics enhances gas yields; steam with oxygen is found the best gasifying agent; while acid pretreatment and catalysts improves gas yields and reduces tar content. The review proposes future research to improve efficiencies and gas yields, thereby providing cleaner and sustainable energy for future generations, while maintaining an effective sustainable waste management scenario. Future work should study techno-economic feasibility, and environmental sustainability (using life cycle assessments) for large scale adoption of energy technologies. Highlights: A critical review of various feedstock blends for co-gasification and co-pyrolysis. Co-conversion modelling, experimental and techno-economic studies are reviewed. Analysis of the impact of blending ratio, catalysts, and pre-treatment on gas yield. Effect of blend of plastic with biomass on efficient utilization. Highlights for the challenges, future prospects and policy implications for technology upscaling.